A study on knowledge, awareness and preventive practice about tuberculosis among medical students in Udaipur, India - More, Balaji D.; Doshi, Chintan; Baghel, Vijay; More, Anju B. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Tuberculosis (TB) is a highly lethal infectious disease causing huge health burden worldwide, commonly involving the respiratory system. Medical students should also be empowered to impart awareness and reduce stigma related to TB. The objective of this study was to evaluate whether educational intervention would affect the level of TB awareness, knowledge, attitude and preventive practice of TB among medical students. Methods: The present study was carried out among the second year medical college students of Pacific Institute of Medical Sciences, Udaipur, India (n=142). A multiple-choice questionnaire of 45 questions was designed in English language, for pre- and post-tests. A 30-minute visual health education was given on TB and the assessment of knowledge, attitude and preventive practice of TB was done by a pre-test and post-test questionnaire. Results: Out of the total 150 student, 142 participated in the study making the response rate 94.66%. The total mean percentage of correct answers for TB knowledge was 48.59 (±20.44) which improved to 69.33 (±17.74) post-training. The total mean percentage of right attitude was 63.036 (±16.46) which improved to 77.06 (±15.58) post-training. The total mean percentage of correct answer for preventive practice were provided by 67.036 (±12.90) which changed to 79.50 (±12.01) post-training. There was significant difference in the knowledge, attitude and preventive practice of students in pre- and post-training tests (p=0.001). Conclusions: Our findings revealed that medical students had poor knowledge. A simple TB education session had a positive influence on knowledge, attitude and preventive practices about TB among them.